An investigation of the ionospheric F region near the EIA crest in India using OI 777.4 and 630.0 nm nightglow observations - Parihar, Navin; Radicella, Sandro Maria; Nava, Bruno; Orue, Yenca Olivia Migoya-; Tiwari, P.; Singh, Rajesh (My University, 2018)
Simultaneous observations of OI 777.4 and OI 630.0 nm nightglow emissions were carried at a low-latitude station, Allahabad (25.5◦ N, 81.9◦ E; geomag. lat. ∼ 16.30◦ N), located near the crest of the Appleton anomaly in India during September–December 2009. This report attempts to study the F region of ionosphere using airglow-derived parameters. Using an empirical approach put forward by Makela et al. (2001), firstly, we propose a novel technique to calibrate OI 777.4 and 630.0 nm emission intensities using Constellation Observing System for Meteorology, Ionosphere, and Climate/Formosa Satellite Mission 3 (COSMIC/FORMOSAT-3) electron density profiles. Next, the electron density maximum (Nm) and its height (hmF2) of the F layer have been derived from the information of two calibrated intensities. Nocturnal variation of Nm showed the signatures of the retreat of the equatorial ionization anomaly (EIA) and the midnight temperature maximum (MTM) phenomenon that are usually observed in the equatorial and lowlatitude ionosphere. Signatures of gravity waves with time periods in the range of 0.7–3.0 h were also seen in Nm and hmF2 variations. Sample Nm and hmF2 maps have also been generated to show the usefulness of this technique in studying ionospheric processes.
Keywords: Nightglow emissions; Ionospheric F region; EIA crest